A monomer-assembly template-directed synthesis of conjugated porous polymer microtubular bundles. Issue 2 (28th October 2019) - Zhang, Wenbei; Cui, Tianlu; Bi, Shuai; Ma, Lie; Lu, Deng; Wu, Dongqing; Zhang, Fan
Abstract : A monomer-assembly template directed strategy to synthesize the conjugated porous polymer with microtubular bundles morphology. Abstract : For porous organic materials, the defined morphology in the micrometre or a larger scale plays an extremely important role in fully exhibiting their molecular-level properties in the bulk phase, thus tuning the synergetic effects of different components and facilitating their fabrication and processing. However, the synthetic strategy towards porous organic materials with well-controlled morphologies is still very limited and full of challenges. Herein, we report a simple self-templated method to construct conjugated porous polymer microtubular bundles in the fused fashion. In the synthesis processes, the monomer 1, 3, 5-benzene-tricarbohydrazide is firstly assembled into crystalline microfiber bundles as the template, which is then condensed with 1, 7- para -formylphenyl-perylene-3, 4, 9, 10-tetracarboxylic diimide via the dynamic covalent acylhydrazon linkage. Upon a quasi-Kirkendall effect and Ostwald ripening process, a conjugated porous polymer featuring smooth microtubular bundles can be essentially constructed. Such defined hierarchical morphology exhibits the substantial co-used tubular walls and orientated channels with sub-micrometre-sized diameters and lengths in tens of micrometers, thus rendering an extremely high accessibility of their redox active sites.